2005
DOI: 10.1038/nature03718
|View full text |Cite
|
Sign up to set email alerts
|

The discovery of a galaxy-wide superwind from a young massive galaxy at redshift z ≈ 3

Abstract: High-velocity galactic outflows, driven by intense bursts of star formation and black hole accretion, are invoked by current theories of galaxy formation 1 to terminate star formation in the most massive galaxies and to deposit heavy elements in the intergalactic medium. From existing observational evidence 2,3 on high-redshift galaxies, it is unclear whether such outflows are localized to regions of intense star formation just a few kiloparsecs in extent, or whether they instead have a significant impact on t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
142
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(152 citation statements)
references
References 22 publications
9
142
1
Order By: Relevance
“…Previous studies of the LABs in the SSA 22 protocluster have suggested that the extended Lyα emission is predominantly due to the heating of the gas rather than cooling (e.g. Bower et al 2004;Geach et al 2005Geach et al , 2009Geach et al , 2014Wilman et al 2005;Smith et al 2008;Webb et al 2009;Colbert et al 2011;Hayes, Scarlata & Siana 2011). By selection, all of our ALMAobserved LABs host X-ray AGNs which, as shown by Geach et al (2009), already provides a potential source of heating for the Lyα emission through photoionization.…”
Section: Star Formation Associated With Lyman-alpha Blobsmentioning
confidence: 55%
“…Previous studies of the LABs in the SSA 22 protocluster have suggested that the extended Lyα emission is predominantly due to the heating of the gas rather than cooling (e.g. Bower et al 2004;Geach et al 2005Geach et al , 2009Geach et al , 2014Wilman et al 2005;Smith et al 2008;Webb et al 2009;Colbert et al 2011;Hayes, Scarlata & Siana 2011). By selection, all of our ALMAobserved LABs host X-ray AGNs which, as shown by Geach et al (2009), already provides a potential source of heating for the Lyα emission through photoionization.…”
Section: Star Formation Associated With Lyman-alpha Blobsmentioning
confidence: 55%
“…Line widths in the extended gas of NVSS J210626-314003 and TXS 2353-003 are FWHM = 300−400 km s −1 (Figs. 1 and 2), more akin to those observed in a quasar illumination cone at z ∼ 2 (Lehnert et al 2009) and Lyα blobs without a powerful central radio source (e.g., Wilman et al 2005;Overzier et al 2013), than to powerful radio galaxies, including the central regions of our two sources here.…”
Section: Imaging Spectroscopy Of the Warm Ionized Gasmentioning
confidence: 56%
“…those in the SA 22 protocluster at z = 3.1) have been extensively observed, and are thought to be driven by starburst events in massive galaxies forming galactic winds (e.g. Ohyama et al 2003;Geach et al 2005Geach et al , 2009Wilman et al 2005;Matsuda et al 2006;Uchimoto et al 2008Uchimoto et al , 2012. Moreover, recent surveys targeting Ly α 'blobs' have also suggested a possible connection between their properties (specifically morphologies) and the environments they reside in (Erb, Bogosavljević & Steidel 2011;Matsuda et al 2011Matsuda et al , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the large velocity widths exceeding ∼1000 km s −1 (van Ojik et al 1997) or absorption across the full extent of the Ly α nebulae (Röttgering et al 1995;van Ojik et al 1996) are also seen in the Ly α nebulae in protoclusters (e.g. Wilman et al 2005;Matsuda et al 2006). Furthermore, observational studies suggest that large fraction of very luminous Ly α blobs ( 10 44 erg s −1 ) are likely to be driven by obscured AGNs (e.g.…”
Section: Introductionmentioning
confidence: 99%